Mitochondrial Porin Is Involved in Development, Virulence, and Autophagy in Fusarium graminearum - Xueqin Han; Qingyi Li; Xuenan Li; Xiang Lv; Li Zhang; Shenshen Zou; Jinfeng Yu; Hansong Dong; Lei Chen; Yuancun Liang (Journal of Fungi, 2022)
Mitochondrial porin, the voltage-dependent anion-selective channel (VDAC), is the most abundant protein in the outer membrane, and is critical for the exchange of metabolites and phospholipids in yeast and mammals. However, the functions of porin in phytopathogenic fungi are not known. In this study, we characterized a yeast porin orthologue, Fgporin, in Fusarium graminearum. The deletion of Fgporin resulted in defects in hyphal growth, conidiation, and perithecia development. The Fgporin deletion mutant showed reduced virulence, deoxynivalenol production, and lipid droplet accumulation. In addition, the Fgporin deletion mutant exhibited morphological changes and the dysfunction of mitochondria, and also displayed impaired autophagy in the non-nitrogen medium compared to the wild type. Yeast two-hybrid and bimolecular fluorescence complementation assays indicated that Fgporin interacted with FgUps1/2, but not with FgMdm35. Taken together, these results suggest that Fgporin is involved in hyphal growth, asexual and sexual reproduction, virulence, and autophagy in F. graminearum.